UPAYA POLISI AIRUD DALAM PENANGGULANGAN TERJADINYA TINDAK PIDANA ILLEGAL FISHING DI WILAYAH PERAIRAN TANJUNGBALAI - Lamhot Gurning; Mangasa Manurung; H. Bachtiar Simatupang (Jurnal Darma Agung, 2020)
Illegal fishing is an act that is very detrimental to a nation and state. The impact will be seen in the short and long term. The government makes handling illegal fishing crimes a very serious concern. This study aims to determine the forms of illegal fishing, AIRUD Police efforts in overcoming and knowing the inhibiting factors of illegal fishing in Tanjungbalai waters. Descriptive analytical research means trying to collect, study, analyze, and describe the illegal fishing countermeasures. The results showed the forms of illegal fishing in Tanjungbalai, namely the use of fishing gear that is in conflict with the laws and regulations (trawl pull). The efforts of AIRUD Police in tackling the occurrence of illegal fishing in the waters of Tanjungbalai are preventive and repressive efforts. Preventive efforts aimed at increasing the intensity of the socialization of laws and regulations to the public, and increasing patrols in waters according to the scope of duties of the Air Force Police Tanjungbalai. Refressive efforts, namely describing decisive action against illegal fishing perpetrators so that it provides a deterrent effect and then provides direction so as not to do the same thing over and over again. The obstacles of AIRUD Police in tackling illegal fishing are the lack of personnel, and the fishermen's HR which are still relatively low, the completeness of facilities and supporting facilities that are still limited in increasing routine patrols in carrying out the tasks of supervision, protection and protecting the special community of fishermen in the waters.